Acceptance Theory of Family Caregiving - Alfredo Feliciano; Evelyn Feliciano; Daisy Palompon; Ferdinand Gonzales (Belitung Raya Foundation, Indonesia, 2022)
Acceptance of roles in the care of older adults by a family caregiver depends on factors emanating from commitment to familial relationships, widespread cultural expectation, and debt of gratitude. This study aims to develop a theory that explains the acceptance of the role of caregiving of the older adults by the family caregiver necessary to predict behavioral adaptation and control caring phenomenon that favors successful meeting of caring expectation across trajectory phases and transitions. A deductive axiomatic approach to theory generation was utilized, resulting in four axioms that served as bases for four propositions. Acceptance Theory of Family Caregiving implies that older adults who expect their children to take care of them as they age have cultural influence and that the acceptance of the role will determine the caregiver’s acceptance of consequences in the form of physical, economical, psychological, and spiritual aspects. In terms of preparedness, family members who accept the possibility of the decline of their older adults are more likely to be assume caregiving roles efficaciously. In the process that family members face in this so-called trajectory caregiving process, resources play a significant role. The developed theory suggests that the care of the older adult in the family caregiving process is determined by the acceptance of role assumption by the family caregiver across trajectory phases. This study highlights the vital implication of acceptance of role assumption to the outcomes of the caregiving process with respect to older adult care, prevention of family caregiver burden, and establishment of strong familial and social relationships.